2013
DOI: 10.12806/v12/i1/r3
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Tools in the Leadership Classroom: Students’ Perceptions of Use

Abstract: Social media is becoming more prevalent in the higher education classroom. As part of an ongoing study, the Department of Agricultural Leadership, Education, and Communications at Texas A&M University surveyed leadership students about their perceptions of their level of comfort and frequency of use of social media tools and the advantages and disadvantages that these students perceived when social media was used in the leadership classroom. A total of 79 students were surveyed in two upper level leadership co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…As technology develops, educators will need to continue exploration on the impact various technologies have toward student engagement. Odom, Jarvis, Sandlin, and Peek (2013), asserted that using technology like social media in leadership classrooms encourages student engagement on the three domains associated with Bloom's Taxonomy. Stressing a self-directed approach to learning, they suggested that certain technologies must stimulate learners cognitively, affectively, and physically.…”
Section: Student Engagement -Three Levelsmentioning
confidence: 99%
“…As technology develops, educators will need to continue exploration on the impact various technologies have toward student engagement. Odom, Jarvis, Sandlin, and Peek (2013), asserted that using technology like social media in leadership classrooms encourages student engagement on the three domains associated with Bloom's Taxonomy. Stressing a self-directed approach to learning, they suggested that certain technologies must stimulate learners cognitively, affectively, and physically.…”
Section: Student Engagement -Three Levelsmentioning
confidence: 99%
“…Kepemimpinan, sampai hari ini dianggap sebagai faktor yang sangat penting dalam sebuah organisasi. Leadership is a relational process and involves connections with individuals (Summer F. Odom, 2013). Kepemimpinan dalam hal ini dimaknai sebagai proses mempengaruhi orang lain dalam suatu komunitas yang diarahkan untuk Vol.…”
Section: B Pembahasanunclassified
“…, Williams and McClure (2010),Wimmer et al (2012),and Odom et al (2013). Acknowledging these benefits, in this article, how the Chernobyl miniseries can be used to illustrate ethical theories is explained.…”
mentioning
confidence: 93%